How Are We to Imagine Them?: Shamanism, Structuralism and The Zoomorphic Series in Dorset Carving - MacRae, Ian J. (Anthropologica, 2013)
Dorset people, particularly the Late Dorset, c. AD 700-1300, have produced an art of significant quality, potency, and power. Dorset art constitutes one of the premiere museum collections in Canada, in any mode, genre or form. This paper examines the widely accepted view of Dorset carving as inextri cably bound with shamanistic practice. Focusing on "naturalistic miniatures," works of zoomorphic realism, it suggests these works may have been vernacular objects, common and part of everyday life, giving expression to the more mundane experi ences of people in the past. This makes them no less emblematic of Dorset social mores, habits, customs, and relations.